Physical and chemical characterizationof fruits of araçá (Psidium guineense Swartz) - de Melo, Aniela Pilar Campos; Seleguini, Alexsander; Santos Veloso, Valquíria da Rocha (Comunicata Scientiae, 2013)
There is a recent interest for the industrial exploitation of the fruits of Psidium guineense Swartz due to the exotic flavor, antioxidant capacity and good consumer acceptance. Considering the lack of information in the literature on physical and chemical parameters of fruits of araçá, aimed to determine these attributes in terms of three classes of ripening fruit (light green, yellowish green and yellow). The physical variables studied were: weight of whole fruit, pulp weight, weight of seed + endocarp, pulp yield, longitudinal diameter, transverse diameter, the relationship between longitudinal and transverse diameter and chemical characteristics: titratable acidity, soluble solids and total soluble solids/titratable acidity. The maturity stages of fruits were not influenced parameters related to the mean weight of whole fruit and share tissue and pulp yield. Yellow fruits are suitable for fresh consumption because of the format, low acidity and high SST/ATT. The araçá has limitations for industrialization due to the low pulp yield and low acidity, and thus may require acidification during processing.